Healthcare Engineering Defined: A White Paper. Issue 4 (18th December 2015) - Chyu, Ming-Chien; Austin, Tony; Calisir, Fethi; Chanjaplammootil, Samuel; Davis, Mark J.; Favela, Jesus; Gan, Heng; Gefen, Amit; Haddas, Ram; Hahn-Goldberg, Shoshana; Hornero, Roberto; Huang, Yu-Li; et al.
Abstract : Engineering has been playing an important role in serving and advancing healthcare. The term "Healthcare Engineering" has been used by professional societies, universities, scientific authors, and the healthcare industry for decades. However, the definition of "Healthcare Engineering" remains ambiguous. The purpose of this position paper is to present a definition of Healthcare Engineering as an academic discipline, an area of research, a field of specialty, and a profession. Healthcare Engineering is defined in terms of what it is, who performs it, where it is performed, and how it is performed, including its purpose, scope, topics, synergy, education/training, contributions, and prospects.